FAKTOR YANG MEMPENGARUHI WARGA BELAJAR MENGIKUTI PROGRAM PENDIDIKAN KESETARAAN PAKET C DI SKB KOTA PEKANBARU - Kurnia Nanda Dipinto; Titi Maemunaty; Widiastuti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research is based on the state conditions of implementation of educational equality program of package C which is seen by factors that affect the learner follow the program at SKB Kota Pekanbaru. The research problems are factors that influence people learning at the educational equality program of package C in the SKB Kota Pekanbaru? The purpose of this study was to determine the factors that affect the learners learn to follow the program of package C . The population in this research as many as 45 people. Then the sample is 45 people and the test sample was 20 learners taken from other SKB. Data collection instrument is a questionnaire with 110 statements and after analyzing the validity of the test, 98 of the item would be valid and 12 items not-valid.. Data analysis through quantitative descriptive analysis. Percentage calculations derived from answer to the research finding of factors that affect the citizens learn to follow the educational program equality package C in SKB Kota Pekanbaru is an external factor with a percentage value of (SS+S) 81,11%. This means that external factors have a very high impact on the willingness of citizens learn to follow the program package C in SKB Kota Pekanbaru.Keywords: Factor affecting, Package C.